2000
DOI: 10.4049/jimmunol.165.3.1410
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Class II Transcriptional Activator-Induced Genes by Representational Difference Analysis: Discoordinate Regulation of the DNα/DOβ Heterodimer

Abstract: Class II transcriptional activator (CIITA) is a master regulator of MHC class II genes, including DR, DP, and DQ, and MHC class II-associated genes DM and invariant chain. To determine the repertoire of genes that is regulated by CIITA and to identify uncharacterized CIITA-inducible genes, we used representational difference analysis. Representational difference analysis screens for differentially expressed transcripts. All CIITA-induced genes were MHC class II related. We have identified the α subunit, DNα, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 59 publications
3
55
1
Order By: Relevance
“…In addition, sensitive real-time RT-PCR data indicate that GM-CSF does not increase DO␤ transcript levels despite increasing DO␣ levels. It has been previously shown that the two chains of DO are differentially regulated, and that in B cells DO␤ expression is influenced by, but not dependent upon, CIITA (26,30). This raises the question of whether DO␣ expressed in the absence, or in excess, of DO␤ can function independently from, or with another partner than, DO␤.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, sensitive real-time RT-PCR data indicate that GM-CSF does not increase DO␤ transcript levels despite increasing DO␣ levels. It has been previously shown that the two chains of DO are differentially regulated, and that in B cells DO␤ expression is influenced by, but not dependent upon, CIITA (26,30). This raises the question of whether DO␣ expressed in the absence, or in excess, of DO␤ can function independently from, or with another partner than, DO␤.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in relative CLIP/class II levels seen following GM-CSF treatment may reflect a change in DM, Ii, and/or DO expression, and this was tested directly. Expression of both the ␣-and ␤-chains of DM and DO was examined, as, at least in the case of DO, the two chains are known to be regulated distinctly (26). As shown in Fig.…”
Section: Gm-csf Increases Total Protein Levels Of Dr Dm II and Do␣mentioning
confidence: 99%
“…These four boxes are present in a tightly conserved arrangement with respect to orientation and spacing, and they function together as a single composite regulatory unit (1,2). A similar sequence arrangement has been conserved in the promoter regions of the Ii, HLA-DM, and HLA-DO genes (7)(8)(9)(10)(11), which code for proteins implicated in the intracellular traffic and peptide loading of MHCII molecules (12,13). The promoters of MHC class I genes also contain a related regulatory module (14).…”
mentioning
confidence: 99%
“…In addition to the genes encoding classical MHCII molecules (HLA-DR, -DP and -DQ), CIITA activates the expression of several genes encoding accessory proteins required for MHCIIrestricted antigen-presentation, namely the invariant chain (Ii), HLA-DM and HLA-DO [17][18][19][20]. It also contributes, albeit to a lesser degree, to classical and nonclassical MHCI expression [4,16,21,22].…”
Section: The Specificity Of Ciitamentioning
confidence: 99%